190 SARS-CoV-2 associated myopericarditis in a patient with previous myocarditis. (8th December 2021) - Amore, Ludovica; Alghisi, Fabio; Vizzardi, Enrico; Cersosimo, Angelica; Cimino, Giuliana; Pancaldi, Edoardo; Pascariello, Greta; D'Aloia, Antonio; Farina, Davide; Gavazzi, Emanuele; Metra, Marco
Abstract: Aims: Severe acute respiratory syndrome coronavirus (SARS-CoV-2) is well described as being responsible for multi-organ involvement and SARS-CoV-2 cardiac involvement was observed since the beginning of the spread of the infection. However, there are no descriptions of acute myopericarditis in patient with previous myocarditis. Methods and results: Cardiac involvement was assessed with electrocardiographic and echocardiographic changes and with increased levels of cardiac high-sensitivity troponin T (hs-cTnT). Diagnosis was confirmed with cardiac magnetic resonance imaging (CMR) and coronary artery disease (CAD) was excluded with coronary angiography. A 53-years-old woman with hypokinetic cardiomyopathy due to a previous myocarditis and recent COVID-19 pneumonia reached the Emergency Department with chest pain and tachycardia in December 2020. Twelve-lead ECG was not conclusive and after detection of significative increase of hs-cTnT she was admitted to the Cardiology Department. Transthoracic echocardiography showed reduction of left ventricle ejection fraction, subendocardial bright appearance and mild pericardial effusion. Coronary angiography excluded obstructive CAD and CMR confirmed diagnosis of recent myocarditis and worsening of left and right ventricular ejection fraction compared to a previous CMR. Patient was treated with evidence-based therapy for heart failure, prednisone, intravenous immunoglobulins, ibuprofen, and colchicine. Cardiac biomarkers reduced within the normal range, symptoms improved, and the patient was discharged asymptomatic and haemodynamically stable. Conclusions: SARS-CoV-2, as already described in literature, can be associated with inflammatory cardiac involvement. This is the first report of SARS-CoV-2 associated myopericarditis in a patient with previous history of myocarditis and recent SARS-CoV-2 pneumonia. In our experience the patient was successfully treated with evidence-based therapy for heart failure and immunomodulation therapy.